Strategic Management as an Introduction to the Development of Managerial Performance in the Lebanese Wrestling Federation - الدكتور فادي الكبي الدكتور ناجي حمود (الرياضة المعاصرة)
All business organizations in the current era, whether public or private, productive or service, face many challenges as a result of rapid and continuous scientific and technical changes and developments, and in the face of these challenges the traditional management, with its processes and means, has become incapable of making the organization competitive, which makes it imperative for these organizations to use All the available contemporary management methods enable it.